Factors shaping the dynamics of housing affordability in Australia 2001-2006 - Wood, G.; Ong, Rachel (Routledge, 2011)
This paper investigates factors shaping the dynamics of housing affordability in Australia over the period 2001–06. Panel model findings indicate that those with children and the unwaged are more prone to persistent housing affordability stress. However, residential moves during spells of housing affordability stress alleviate housing cost burdens. Survival in affordable housing has become progressively more difficult over the 2001–06 timeframe, an unsurprising finding given a house price boom over the period of analysis. Residential moves are again influential, but those made by households during a spell in affordable housing are associated with the onset of housing affordability stress.